2008
DOI: 10.3406/cchav.2008.1526
|View full text |Cite
|
Sign up to set email alerts
|

L’héroïsme au féminin chez Shakespeare et Nicolas de Montreux

Abstract: Nicolas de Montreux (1561?-1608?, pseudonym «Ollenix du Mont-Sacré») was an eminent, and prolific, literary figure when he wrote his tragedy Cléopâtre (15047). He was also politically engaged in the Holy League in the service of the Duke of Mercœur, governor of Brittany, and one may associate with the militant and spirited Duchess his interest in noble heroines who prefer death to humiliation. The tragedies of Cleopatra by Shakespeare and Samuel Daniel have sufficient points in common with Montreux’s work to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… On the details of the performance of Arimène , see Lawrenson (1956). Following him, Hillman has argued for the likelihood of the performance of two of Montreux’s other tragedies from this period, Cléopâtre and Isabelle , in 1594 (Hillman, 2008, 75 n. 6) which, like La Sophonisbe , deal with the glorified suicide of a female figure, further supporting the likelihood of a performance of La Sophonisbe at the court of the duke in the 1590s. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… On the details of the performance of Arimène , see Lawrenson (1956). Following him, Hillman has argued for the likelihood of the performance of two of Montreux’s other tragedies from this period, Cléopâtre and Isabelle , in 1594 (Hillman, 2008, 75 n. 6) which, like La Sophonisbe , deal with the glorified suicide of a female figure, further supporting the likelihood of a performance of La Sophonisbe at the court of the duke in the 1590s. …”
mentioning
confidence: 99%
“… For example the crushed dreams of sovereignty by the duke of Mercæur in the figure of Siphax (Buron, 2009, 36–37) or in the figure of Massinisse, the alienation of the nobility more generally in the face of the new absolute monarch, Henri IV (Buron, 2020a, 363, 376–379, 381). Following this, Richard Hillman has suggested that Montreux’s chaste heroines such as Sophonisbe be read a reflection on the duke’s wife, Marie de Luxembourg (Hillman, 2008, 74, 86). For more on Montreux’s political affiliation with the duke of Mercæur see also Mathorez (1912) and Daele (1946).…”
mentioning
confidence: 99%